Antimicrobial activity of new bicyclic lactones with three or four methyl groups obtained both synthetically and biosynthetically - Katarzyna Wińska; Małgorzata Grabarczyk; Wanda Mączka; Barbara Żarowska; Gabriela Maciejewska; Mirosław Anioł (Journal of Saudi Chemical Society, 2018)
Ten new derivatives of isophorone were obtained through a five-step synthesis. Among the products were several unsaturated, bicyclic lactones with three or four methyl groups. These lactones were used as the substrates for biotransformation mediated by selected fungal strains (Fusarium species, Syncephalastrum racemosum, Cunninghamella japonica, Penicillium species, Absidia species, and Pleurotus ostreatus). Four new hydroxylactones were obtained as a result of biotransformation. Because the unsaturated lactone with four methyl groups was a diastereoisomeric mixture, a structural analysis was conducted. The hydroxylactones were also included in this analysis. Both the unsaturated lactones and hydroxylactones were examined for their antimicrobial activity. It was found that some of these compounds exhibited growth inhibition against pathogenic strains of bacteria (Staphylococcus aureus, Pseudomonas fluorescens), yeasts (Candida albicans) and filamentous fungi (Alternaria sp., Penicillium sp.). All obtained compounds were also subjected to scent analysis.